Is zinc concentration in toxic phase plasma related to dengue severity and level of transaminases? - Kamolwish Laoprasopwattana; Chonthicha Tangcheewawatthanakul; Wanutsanun Tunyapanit; Rassamee Sangthong (Public Library of Science (PLoS), 2013)
OBJECTIVE: To determine the relationship between plasma zinc values and the severity of dengue viral infection (DVI) and DVI-caused hepatitis. METHODS: A prospective cohort study was conducted during 2008-2010 in hospitalized children aged <15 years confirmed with DVI. Complete blood count, aspartate aminotransferase (AST), alanine aminotransferase (ALT), and zinc values (mcg/dL) were determined twice: first during the toxic phase (Zn1) and secondly two weeks after recovery (Zn2). RESULTS: 39 patients were enrolled with a mean age of 9.7 ± 3.7 years, and 15/39 diagnosed with dengue shock syndrome (DSS). Zn1 values were lower than Zn2 values [median (IQR): 46.0 (37.0, 58.0) vs 65.0 (58.0, 81.0) mcg/dL, respectively, p <0.01]. Zn1 but not Zn2 values had a negative correlation with AST and ALT (rs = -0.33, p = 0.04 and rs = -0.31, p = 0.05, respectively). Patients with DSS had lower Zn1 but not Zn2 values compared with non-DSS patients [median (IQR) Zn1, 38.0 (30.0, 48.0) vs 52.5 (41.2, 58.7), p = 0.02; Zn2, 61.0 (56.0, 88.0) vs 65.0 (59.5, 77.5), respectively, p = 0.76]. Zn1 values showed a decreasing trend across increasing dengue severity groups (p = 0.02). Age <5 years and DVI-associated diarrhea were associated with low Zn1. CONCLUSION: Children who had a higher grade of dengue disease severity and liver cell injury had lower Zn1 values. Low Zn1 values were probably caused by loss from diarrhea and from zinc translocating to liver cells.